Ethical seed sourcing is a key issue in meeting global restoration targets - Nevill, Paul; Cross, Adam; Dixon, Kingsley (Cell Press, 2018)
© 2018 Elsevier Ltd The global demand for restoration has increased orders of magnitude in the last decade, and hundreds of thousands of tonnes of native seed are required to feed this restoration engine [1] (Figure 1). But where are all the seeds required by restoration going to come from? Wild seed resources continue to be depleted by habitat loss, land degradation and climatic change, and over-collection of seed from wild populations threatens to erode these resources further. Ethical seed sourcing for restoration now represents a core issue in responsible restoration practice. Solutions include the introduction of regulatory frameworks controlling seed sourcing from wild populations, the development of seed farming capacity and advancement of seed enhancement technologies and precision delivery systems reducing seed wastage. Nevill et al. argue that wild-harvesting of seed at scales required to meet global restoration demands is not sustainable. Solutions proposed include investment in native seed farms, introduction of a regulatory framework to ensure the integrity of seed quality, development of seed enhancement and precision seeding technologies.